2021
DOI: 10.1111/anae.15527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐flow vs. low‐flow nasal plus mouthguard oxygen therapy on hypoxaemia during sedation: a multicentre randomised controlled trial

Abstract: Whether high-flow vs. low-flow nasal oxygen reduces hypoxaemia for sedation during endoscopic retrograde cholangiopancreatography is currently unknown. In this multicentre trial, 132 patients ASA physical status 3 or higher, BMI > 30 kg.m -2 or with known or suspected obstructive sleep apnoea were randomly allocated to high-flow nasal oxygen up to 60 l.min -1 at 100% F I O 2 or low-flow nasal oxygen at 4 l.min -1 . The low-flow nasal oxygen group also received oxygen at 4 l.min -1 through an oxygenating mouthg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(60 citation statements)
references
References 37 publications
0
60
0
Order By: Relevance
“…Finally, the full texts of 14 articles were evaluated, and 7 studies were excluded: 1 was a pediatric patient study, 1 was a comment paper, 3 were protocols, 2 were observational studies. In total, 7 RCTs [ 21 24 , 26 28 ] were eligible in our meta-analysis, which ultimately included 2998 patients. The flowchart of the study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, the full texts of 14 articles were evaluated, and 7 studies were excluded: 1 was a pediatric patient study, 1 was a comment paper, 3 were protocols, 2 were observational studies. In total, 7 RCTs [ 21 24 , 26 28 ] were eligible in our meta-analysis, which ultimately included 2998 patients. The flowchart of the study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Trials took place across North America, Europe, Asia, and Australia. HFNC in two studies was used during ERCP procedural sedation [ 22 , 24 ], and others were used during esophagogastroduodenoscopy procedural sedation. In 3 of 7 articles, procedures were performed on high risk of hypoxemia subjects [ 23 , 24 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations